2020
DOI: 10.31234/osf.io/tpjes
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An optimal dichotic-listening paradigm for the assessment of hemispheric dominance for speech processing

Abstract: Dichotic-listening paradigms are widely accepted as non-invasive test of hemispheric dominance for language processing and represent a standard diagnostic tool for the assessment of developmental auditory and language disorders. Despite of its popularity in research and clinical settings, dichotic paradigms show comparatively low reliability, significantly threatening the validity of conclusions drawn from the results. Thus, the aim of the present work was to design and evaluate a novel, highly reliable dichot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Effect sizes were expressed as Cohen's d or proportion explained variance (η 2 ). The data can be downloaded from the associated OSF platform [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect sizes were expressed as Cohen's d or proportion explained variance (η 2 ). The data can be downloaded from the associated OSF platform [45].…”
Section: Discussionmentioning
confidence: 99%
“…One run of the paradigm took approximately 12 min including instructions, and short breaks between the blocks. The paradigm is available as part of the OptDL Project on the OSF platform [45].…”
Section: Stimulus Materials and Paradigm Designmentioning
confidence: 99%
“…As with the visual half-field paradigm, the test-retest reliability of dichotic listening paradigms has been far from optimal (Kelley & Littenberg, 2019;Voyer, 1998). However, recent data from Westerhausen and Samuelsen (2020) indicated that when designed optimally, the dichotic listening paradigm can be reliable. First, based on a review of the published literature, Westerhausen and Samuelsen outlined eight design features that should be used in an optimal dichotic listening paradigm and explained their justification for each.…”
Section: Lateralized Auditory Verbal Processingmentioning
confidence: 99%
“…We further showed (see Figure 4) that there was little decline in reliability with 85 trials, and with as few as 60 trials, the current implementation of the dichotic listening task yielded a test-retest correlation higher than r = .65, suggesting that those who wish to use this paradigm in the future could use a smaller number of trials. It would be of interest to extend this line of work to use the modified version of dichotic listening described by Westerhausen and Samuelsen (2020), which had even higher reliability. Of course, it is important to screen for adequate use of stereo headphones when devising online versions of the task.…”
Section: Discussionmentioning
confidence: 99%
“…As with the visual half-field paradigm, the test-retest reliability of dichotic listening paradigms has been far from optimal (Voyer, 1998;Kelley & Littenberg, 2019). However, recent data from Westerhausen and Samuelsen (2020) indicated that when designed well, the dichotic listening paradigm can be reliable. First, based on a review of the published literature, Westerhausen and Samuelsen outlined eight design features that should be used in an optimal dichotic listening paradigm and explain their justification for each.…”
Section: Dichotic Listeningmentioning
confidence: 99%